1982
DOI: 10.1139/f82-173
|View full text |Cite
|
Sign up to set email alerts
|

Immigration of Juvenile Coho Salmon (Oncorhynchus kisutch) into Riverine Ponds

Abstract: Riverine ponds on the Olympic Peninsula provide important winter refuge for juvenile coho salmon (Oncorhynchus kisutch). A total of 9530 juvenile coho migrated into two riverine ponds of the Clearwater River in 1977, principally during fall freshets. Extensive movement by marked fish (as much as 32.6 km downstream) before entering the ponds suggests that a system-wide approach to habitat management is important in maintaining freshwater production potential of large river systems.Key words: juvenile coho, immi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
66
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 0 publications
11
66
1
Order By: Relevance
“…Logging activities lower the considerable to complete reductions in densities but were recolonized by small numbers of coho salmon by mid-to late winter. Following a series of winter freshets, Peterson (1982) found the majority of marked juvenile coho salmon sheltering in riverine ponds as far as 33 kilometers downstream from their residential habitats.…”
Section: Human Alterations Of Winter Disturbances and Refugiamentioning
confidence: 99%
See 1 more Smart Citation
“…Logging activities lower the considerable to complete reductions in densities but were recolonized by small numbers of coho salmon by mid-to late winter. Following a series of winter freshets, Peterson (1982) found the majority of marked juvenile coho salmon sheltering in riverine ponds as far as 33 kilometers downstream from their residential habitats.…”
Section: Human Alterations Of Winter Disturbances and Refugiamentioning
confidence: 99%
“…The literature shows a bias in describing physical disturbances to fish and their habitats and neglects the idea that riverine fish communities could also be subject to purely biological Articles to conserve the remaining refugia, to restore those that have been lost, and to reestablish the connectivity between residential habitats and refugia (Skeesick 1970, Bond andLake 2005). A catchmentwide perspective has to be applied, given the large-scale significance of refugia (Peterson 1982). Because many important refugia from winter disturbances form only temporarily (Tschaplinski andHartman 1983, Brown RS et al 2001), they are often underappreciated and are therefore neglected in management and legislation.…”
Section: Linking Winter Ecology and Disturbance Researchmentioning
confidence: 99%
“…Sommer et al 2001), off-channel ponds (e.g. Peterson 1982), natal tributaries (e.g. Johnson et al 1992), and non-natal tributaries (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that off-channel habitats of various types are important rearing habitat for juvenile fish [Peterson, 1982;Swales and Levings, 1989]. Two anadromous species, steelhead trout (Oncorhynchus kisutch) and chinook salmon (Oncorhynchus tshawytscha), were listed in 1999 as threatened species on the upper Willamette River and have been observed preferentially using alcove habitats during winter months (C. Andrus, unpublished data, 1999 To inform future water quality and habitat studies and to improve river system management, this study addresses two questions: (1) Are transient storage in general and hyporheic flow in particular significant processes on the upper Willamette River?…”
Section: Introductionmentioning
confidence: 99%